Dapagliflozin: a sodium glucose cotransporter 2 inhibitor in development for type 2 diabetes - Tahrani, Abd A. (Springer Healthcare Communications, 2011)
Type 2 diabetes mellitus (T2DM) is a growing worldwide epidemic. Patients face lifelong therapy to control hyperglycemia and prevent the associated complications. There are many medications, with varying mechanisms, available for the treatment of T2DM, but almost all target the declining insulin sensitivity and secretion that are associated with disease progression. Medications with such insulin-dependent mechanisms of action often lose efficacy over time, and there is increasing interest in the development of new antidiabetes medications that are not dependent upon insulin. One such approach is through the inhibition of renal glucose reuptake. Dapagliflozin, the first of a class of selective sodium glucose cotransporter 2 inhibitors, reduces renal glucose reabsorption and is currently under development for the treatment of T2DM. Here, we review the literature relating to the preclinical and clinical development of dapagliflozin.